LINGUOCULTURAL ANALYSIS OF PHRASES WITH ADJECTIVE COMPONENTS IN ENGLISH AND UZBEK - Mamurova Shahlo (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article is a section of lexicology dedicated to the field of phraseology, in which phraseology with qualitative components in English and Uzbek linguistics is mainly analyzed from a linguistic and cultural point of view, and the mentality, culture, customs and traditions of a certain nation are studied. Valuable information is given about the phraseological units reflected in it. Studying phrases in both languages, revealing their semantic-grammatical and functional stylistic features determines the relevance of this work. However, expressions with adjective components are an unexplored field within these languages. It is known that expressions are inextricably linked with the spirituality, culture, customs, lifestyle and history of the people who own the language. Based on this point of view, about 50 phrases containing adjectives were studied in the article, and the manifestation of the culture of the two nations in the language, their mutual influence and connection were considered. The opinions of linguists were studied and general conclusions were given to them.